Endeavors to foster Healthy Adolescent Free from Anemia: from Nutritional Perspective - Eka Febriyanti; Huwainan Nisa Nasution; Ratih Yulistika Utami (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Anemia in adolescent girls in Indonesia is one of the health focuses related to its high prevalence and the enormous impact that can be caused, such as productivity problems and even affecting pregnancy and the fetus in the future. Nutrition is one of the causes of this condition and other factors such as nutritional status, blood loss through menstruation, and rapid growth in adolescents. This community service activity aims to provide education about anemia and conduct screening for adolescent girls at the Aisyiyah Orphanage in Medan City. From the examination of 24 participants, it was found that one person had anemia which was followed up with education and administration of iron supplements for 12 weeks. The material presented emphasized the importance of consuming a balanced nutritious diet rich in iron, consuming food sources of vitamin C, and avoiding coffee, tea, and milk when eating. In addition, posters regarding nutrition in anemia were also posted to strengthen adolescents' awareness and motivation in alleviating anemia. This activity has a positive impact on participants because it increases their understanding of anemia so that they can change their health behavior